ln(5x-2)-ln(x+3)=2

Simple and best practice solution for ln(5x-2)-ln(x+3)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(5x-2)-ln(x+3)=2 equation:


Simplifying
ln(5x + -2) + -1ln(x + 3) = 2

Reorder the terms:
ln(-2 + 5x) + -1ln(x + 3) = 2
(-2 * ln + 5x * ln) + -1ln(x + 3) = 2
(-2ln + 5lnx) + -1ln(x + 3) = 2

Reorder the terms:
-2ln + 5lnx + -1ln(3 + x) = 2
-2ln + 5lnx + (3 * -1ln + x * -1ln) = 2
-2ln + 5lnx + (-3ln + -1lnx) = 2

Reorder the terms:
-2ln + -3ln + 5lnx + -1lnx = 2

Combine like terms: -2ln + -3ln = -5ln
-5ln + 5lnx + -1lnx = 2

Combine like terms: 5lnx + -1lnx = 4lnx
-5ln + 4lnx = 2

Solving
-5ln + 4lnx = 2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-2 + -5ln + 4lnx = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + -5ln + 4lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 5(2+p)=17.5 | | 5x+45-89=-90+41 | | 3+2p=7 | | -5(2(2)+7)+2(9)+5(-5)= | | 5(z-1)-20=0 | | Y=2ln(3x-1)-2 | | -10x^2-6x-12=0 | | -4=-8x+2 | | 9(4(-25)-3)= | | ln(x-6)=24 | | 90t=450t | | 9t^2-54=0 | | -24r+6= | | 9(-5)(2)+3(-25)-7(4)+8(-5)(2)-12= | | Y=-8sin(7x) | | 8=2d-12 | | -7x-y+z=-12 | | x-9=.75x | | (5x+5)+(-6x+8)= | | x^2+y^2+18x+12y=11 | | 8b+3=5b+7 | | 3(3x-7)=81(12x-3x) | | 2/12= | | e^7x=10 | | -7(3(-5)-4)+2= | | -4(3(-5)-5(2)-7)= | | 2-2x-6x=26 | | 5r^3+r^2=80r+16 | | 2h-1=1 | | 5(2(-5)+6)-12(-5)= | | -2(3-7a)=-38+6a | | F(x)=2x^2-5x-25 |

Equations solver categories